Konseling Individu Teknik Assertivinnes Training Terhadap Kemampuan Komunikasi Asertif Remaja - Wulandari; Anikoh, Indifatul (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
In the process of development, adolescents often have difficulty in expressing their emotions and opinions. The feelings of embarrassment and discomfort felt by adolescents have an impact on the difficulty in conveying arguments caused by lack of communication skills. This study aims to increase understanding for adolescents that assertive communication is important in everyday life, so that it is easier to socialize and build communication with people around them. This research method uses descriptive qualitative research methods. Data collection techniques used are interviews, observations and documentation. Data analysis used is data reduction, data presentation, and drawing conclusions. The data validity technique uses triangulation of data sources, namely by comparing the results of interviews, observations, and documentation.